Numerical study on biomass model compound gasification in a supercritical water fluidized bed reactor. (29th September 2015) - Su, Xiaohui; Jin, Hui; Guo, Simao; Guo, Liejin
Abstract: Supercritical water fluidized bed gasifier is a new promising reactor for thermochemical conversion of wet biomass. However, there exists many troubles in directly measuring the process details in the reactor due to the extreme operating condition. A comprehensive 3-D numerical model of hydrodynamics based on the two-fluid model accompanying with heat transfer and chemical reactions kinetics is developed in this study to simulate glucose gasification in a supercritical water fluidized bed reactor in a temperature range 823–923 K under pressure 25 MPa. The particle collision is described by the kinetic theory of granular flow. The gasification reaction rates are determined by Arrhenius equation. The flow behavior of supercritical water-particle flow, temperature and reaction rates distribution, gas composition profiles in the bed were predicted and assessed against available published experimental data. The particles show a homogeneous fluidization in supercritical water fluidized bed. Results show that the current three dimensional gasification model can reasonably describe the reacting flow behavior in the supercritical water fluidized bed reactor, which may provide a convenient and low-cost way for the reactor design and optimization. Highlights: Simulation of biomass gasification in a SCW fluidized bed was performed. Hydrodynamics, heat transfer and chemical reaction were all incorporated. The particles showed a homogeneous fluidization in SCW fluidized bed. Strategy for reactor design and optimization was presented.